EMOTIONAL DESIGN OF CHINESE ANIMATION IMAGE BASED ON AUDIENCE’S PSYCHOLOGICAL LEVEL - CHEN , L.; Khynevych, R. (Art and Design, 2023)
Рurpose. Study the underlying logic of shaping the image of Chinese animation with the help of emotional design, on the basis of respecting and understanding the transformation of audience’s psychological needs. Starting from the psychological level of Chinese animation audience, analyze the aesthetic tendency and characteristics of Chinese animation image-building. Methodology. In the way of combining theory with demonstration, the relationship between the psychological transformation of animation audience and animation image is deeply discussed. It includes case analysis and comparative analysis. Results. Animation creation is deeply influenced by the audience’s psychology and emotion. On the basis of understanding the audience’s aesthetic experience, have been analyzed the different emotional needs of Chinese animation images in the audience’s instinctive level, behavioral level and reflective level, which are embodied in the tendency of "popularization", the combination of realism and freehand brushwork. By comparing the successful and classic animation images, have been researched the internal emotional connection between the audience and the animation images, indicating a tendency for future creation of animated images. Scientific novelty. In terms of studying the image of Chinese animation, this paper proposes to correspond the three levels of emotional design theory to different levels of emotional needs of animation audiences, and focuses on summarizing new phenomena in animation image from the perspective of audience psychology. Practical significance. Relying on the emotional design of animation images caused by the psychological needs of the audience, this paper makes an in-depth analysis of Chinese animation image design, providing new ideas for the design and creation of animation images, opening up a new situation for the animation market in China and creating new animation images for more audiences.